PEMANFAATAN DAUN GAMAL SEBAGAI PUPUK ORGANIK CAIR (POC) UNTUK MENINGKATKAN PERTUMBUHAN DAN PRODUKSI TANAMAN KUBIS BUNGA (Brassica oleracea L.) PADA TANAH PODSOLIK - Novriani, Novriani (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2016)
This study aims to investigate the response of growth and yield of cauliflower on the provision of GliricidiaLeaves Liquid Organic Fertilizer and to determine the concentration of Gliricidia Leaves Organic Liquid Fertilizerfor the best growth and production of cauliflower. This research was conducted in experiment garden Faculty ofAgriculture Baturaja University, located in the sub district Baturaja Timur. The research started since May to July2015. Data was analyzed by using non factorial completely randomized design, with 5 treatments were repeated 5times, in order to get 25 units of treatment. The treatment in this study was P0 = Control, P1 = POC Leaves ofGliricidia 15 ml / liter of water, P2 = POC Leaves of Gliricidia 25 ml / liter of water, P3 = POC Leaves of Gliricidia 35ml / liter of water, P4 = POC Leaves of Gliricidia 45 ml / liter water. The results of this research was the givingGliricidia Leaves Liquid Organic Fertilizer significantly affect the growth and production. Giving POC concentrationof 45 ml / liter of water (P4) is the best treatment to improve the growth and yield of cauliflower. P4 treatmentenhances growth of cauliflower interest at 12.86% and production by 135.22% if compared to P0 treatment, withthe production of cauliflower as 10.38 tonnes per acre.